Public Relations Strategy of Perumda Tirta Pakuan, Bogor City in Managing Instagram @perumdatirtapakuan as a Means of Publishing Information - Andriani, Deswita Zahra; Saleh, Amiruddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Public relations plays a strategic role in bridging communication between organizations and the public. This study aims to describe the public relations strategy of Perumda Tirta Pakuan, Bogor City, in managing its Instagram account @perumdatirtapakuan as a medium for disseminating information to the public. The research employs a qualitative approach with a descriptive design. Data collection techniques include direct observation, active participation, in-depth interviews, documentation, and literature review. The strategy is implemented through five main pillars: flexible monthly content planning, production and packaging of informative and educational content, routine performance evaluation, two-way communication management through active responses, and rapid, transparent crisis communication handling. The findings indicate that the majority of the account's followers are housewives, leading to the use of emotional and practical approaches as the core strategy. The Instagram account @perumdatirtapakuan functions not only as a promotional medium but also as the digital face of Perumda Tirta Pakuan, reflecting transparency, service efficiency, and accountability to public needs. This strategy may serve as a model for other public institutions.